Predictors of Psychotherapy Use among Community-Dwelling Older Adults with Depressive Symptoms. Issue 2 (14th March 2016) - Nurit, Gur-Yaish; Dana, Prilutzky; Yuval, Palgi
ABSTARCT: Objectives : The present study investigates the applicability of the behavioral model of health service use (Andersen, 1995) to the predicting of psychotherapy use among older adults. Methods : Sample was obtained, using a random-digit dialing methodology, from the older Jewish population in Israel. The final sample consisted of 509 respondents with an average age of 74.08 (SD = 5.89). The telephone interviews were conducted in the first week of August 2011, by experienced interviewers, in Hebrew or Russian, using a structured questionnaire. Results : After adjusting for age, gender, education, marital status, religiosity, health status, and economic status in the first step, binary logistic regression revealed that higher depressive symptoms, positive attitudes toward psychological treatment, primary physician referral, and accessibility of psychological services were all related to higher odds ratios for seeking psychological treatment. Conclusions : The present study integrated previously identified precursors of mental health service use into one model predicting psychotherapy use among community-dwelling older adults. The model suggests that the point of entry to psychotherapy is not limited to one source and that individuals' need, their attitudes, accessibility of services, and their primary physicians' referral are all useful facilitators of psychotherapy use.